THE СONTRIBUTION OF WOMEN WRITERS IN ENGLISH LITERATURE - Olimova Madina Yorqinjon qizi; Igamberdiyeva Shahnoza Adxamovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article studies the significance of the female writers in English writers. The results to be achieved in this research will be very helpful in working out effective and useful for teaching English literature in the future. The analysis of world women writers ‘literary works would depict the changes referred to women‘s right to take part in public life.